Hierarchical Structures in Livestock Trade Networks—A Stochastic Block Model of the German Cattle Trade Network - Brzoska, Laura; Fischer, Mareike; Lentz, Hartmut H. K. (Frontiers in Veterinary Science, 2020)
Trade of cattle between farms forms a complex trade network. We investigate partitions of this network for cattle trade in Germany. These partitions are groups of farms with similar properties and they are inferred directly from the trade pattern between farms. We make use of a rather new method known as stochastic block modeling (SBM) in order to divide the network into smaller units. SBM turns out to outperform the more established community detection method in the context of disease control in terms of trade restriction. Moreover, SBM is also superior to geographical based trade restrictions and could be a promising approach for disease control.